Risk factors for invasive fungal infections in adult patients with hematological malignancies and/or stem cell transplant: a systematic review and meta-analysis - Emmanuelle Gras; Patricia Monzo-Gallo; Loris Azoyan; Carolina Garcia-Vidal; Fanny Lanternier; Eolia Brissot; Juliette Guitard; Karine Lacombe; Agnès Dechartres; Laure Surgers (Scientific Reports)
Abstract Improving prevention and treatment strategies for invasive fungal infections (IFI) is essential to reduce associated morbidity and mortality. We performed a systematic review and meta-analyses to assess factors associated with IFI in adult patients with hematological malignancies and/or hematopoietic stem cell transplantation (HSCT). Data sources. We searched PubMed, Embase, CENTRAL and the grey literature from 01/01/2002 to 08/02/2024. Study eligibility criteria. Eligible studies were case-control or cohort studies including adult patients with hematological malignancies and/or HSCT and reporting risk factors for IFI. Participants. Adult patients with hematological malignancies and/or HSCT. Assessment of risk of bias. Risk of bias assessment was assessed independently using the Critical Appraisal Skills Programme checklists for cohort studies and case-control studies. Methods of data synthesis. Study selection and data extraction were done independently. Adjusted estimates were pooled using random effects models. Among 12 624 references identified, 69 studies (reporting 2917 IFI) were included in the systematic review, 20 of which were included in meta-analyses. Factors independently associated with IFI included previous allo-HSCT (pooled aHR 3.21 [95%CI 1.54–6.71]), especially with a haploidentical donor (pooled aHR 2.41 [95%CI 1.27–4.57]), acute graft vs. host disease (aGvHD) ≥ 2 (pooled aHR 2.59 [95%CI 1.36–4.90]), corticosteroids (pooled aOR 2.84 [95%CI 1.42–5.70]) or T-cell depleting agents (pooled aOR 2.73 [95%CI 1.61–4.64]). Antifungal prophylaxis was a protective factor for IFI (pooled aOR 0.20 [95%CI 0.13–0.28]). The identification of factors independently associated with IFI may help to stratify IFI risk among hematological patients. Registration: PROSPERO, CRD42023429103.